Hi‐Fi SELEX: A high‐fidelity digital‐PCR based therapeutic aptamer discovery platform. Issue 8 (9th April 2015) - Ouellet, Eric; Foley, Jonathan H.; Conway, Edward M.; Haynes, Charles
ABSTRACT Current technologies for aptamer discovery typically leverage the systematic evolution of ligands by exponential enrichment (SELEX) concept by recursively panning semi‐combinatorial ssDNA or RNA libraries against a molecular target. The expectation is that this iterative selection process will be sufficiently stringent to identify a candidate pool of specific high‐affinity aptamers. However, failure of this process to yield promising aptamers is common, due in part to (i) limitations in library designs, (ii) retention of non‐specific aptamers during screening rounds, (iii) excessive accumulation of amplification artifacts, and (iv) the use of screening criteria (binding affinity) that does not reflect therapeutic activity. We report a new selection platform, High‐Fidelity (Hi‐Fi) SELEX, that introduces fixed‐region blocking elements to safeguard the functional diversity of the library. The chemistry of the target‐display surface and the composition of the equilibration solvent are engineered to strongly inhibit non‐specific retention of aptamers. Partition efficiencies approaching 106 are thereby realized. Retained members are amplified in Hi‐Fi SELEX by digital PCR in a manner that ensures both elimination of amplification artifacts and stoichiometric conversion of amplicons into the single‐stranded library required for the next selection round. Improvements to aptamer selections are first demonstrated using human α‐thrombin as the target. Three clinical targets (human factors IXa, X, and D) are then subjected to Hi‐Fi SELEX. For each, rapid enrichment of ssDNA aptamers offering an order‐nM mean equilibrium dissociation constant (Kd) is achieved within three selection rounds, as quantified by a new label‐free qPCR assay reported here. Therapeutic candidates against factor D are identified. Biotechnol. Bioeng. 2015;112: 1506–1522. © 2015 Wiley Periodicals, Inc.